Multiple mandibular ossifying fibromas in a yearling Belgian Draught horse filly. (22nd September 2014) - Crijns, C. P.; Vlaminck, L.; Verschooten, F.; van Bergen, T.; De Cock, H. E.; Huylebroek, F.; Pool, R.; Gielen, I.
Summary A yearling Belgian Draught horse filly was presented with a history of bilateral, progressive, painful swelling of the mandible, fever and anorexia. Radiographs and computed tomographic images showed an expansile lesion with a coalescing, well‐defined cystic pattern at the level of the horizontal ramii of the mandible. The histopathological findings confirmed the diagnoses of bilateral, multiple ossifying fibroma. This report indicates that ossifying fibroma should be included in a differential diagnosis if multiple expansile lesions of the jaw are present.